Enhancing Students’ Practical Skills: The Effect of QR-Code Based E-Jobsheet on Electrical Installation Learning Outcomes - Mustofa, Amirudin; Haryudo, Subuh Isnur; Achmad, Fendi; Zuhrie, M. Syariffuddien (Edukasi, 2024)
Education is a conscious and planned effort to create a conducive learning atmosphere and a structured learning process so that students actively develop their potential. This study aimed to determine whether there was an effect of QR-CODE-based e-job-sheet on the learning outcomes of electrical lighting installation practices for class XI TITL students in the electrical lighting installation subject at SMK Negeri 1 Driyorejo. This study used a quantitative approach with a pre-experimental design, specifically using a one group pretest-posttest format. The population for this study comprised Class XI TITL students engaged in electrical lighting installation, with a sample size of 35 students drawn from this population. The sample used was a saturated sample, a sampling technique that included all members of the population as participants. The instruments for data collection were in the forms of a job-sheet and an observation sheet for students' psychomotor assessment which were first validated by 3 validators consisting of an electrical engineering lecturer and two TITL teachers. The results of this study found that the significance value (Sig.) amounting to 0.000 this means that the value (Sig.) is greater than 0.05 this means. H0 is rejected and H1 is accepted. While when viewed from the t test value it is known that the t-count value = 4.359 and the t-table value = 2.034 this means. H0 is rejected H1 is accepted. Thus, it could be concluded that there was a significant effect of using e-job-sheet on the psychomotor learning outcomes of students in class XI TITL in the subject of electrical lighting installation.